FAKTOR-FAKTOR YANG MEMENGARUHI KONSERVATISME (Studi pada Perusahaan Manufaktur yang Terdaftar di BEI 2010-2014) - Barkah Susanto; Tiara Ramadhani (Fakultas Ekonomika dan Bisnis, Universitas Stikubank, 2016)
This study is aimed at examining the effects of leverage, company size, capital intensity, liquidity, and growth opportunities toward conservatism in the manufacturing companies listed on the Indonesian Stock Exchange (BEI). This study sample consisted of 22 manufacturing companies in BEI taken through the use of purposive sampling method. The analytical tool implemented was SPSS. The findings provide evidences that company size and capital intensity have positive influence on conservatism. Meanwhile the leverage, liquidity and growth opportunities have no positive effects on conservatism. Keywords: Conservatism, leverage, company size, capital intensity, liquidity, growth opportunities